Anatomic Study of Craniocervical Junction and Its Surrounding Structures in Endoscopic Transoral-Transpharyngeal Approach. Issue 7 (October 2018) - Zhong, Sheng; Ren, Jiaxin; Zhang, Yuan; Li, Weihang; Li, Hui; Song, Siying; Zhao, Gang; Cheng, Ye
Abstract : Purpose: This study aims to provide accurate and comprehensive data of craniocervical junction and its peripheral structures in order to provide a profound insight of craniocervical junction as well as to avoid complications during surgical procedures related to it. Methods: Computed tomographic angiography (CTA) images of 120 individuals were reviewed, the measurements were performed on coronal, sagittal, and axial planes after 3-dimensional volume reconstruction. The authors measured pharyngeal tubercle, foramen magnum, and tuberculum anterius atlantis, which located based on the position of incisor. The anatomic features of other important bony landmarks, internal carotid artery, and vertebral artery were also fully studied so as to avoid being injured during the transoral-transpharyngeal procedure. Results: During the endoscopic surgery to craniocervical junction, the bending angle of neuroendoscopy should be 14.27 ± 4.51° and the entering depth should be about 72.57 ± 8.72 mm. It is safe to work within the angle of 77.73 ± 3.15° in axial plane and the safe penetration width from the axial midline is 20.05 ± 3.11 mm in the level of foramina magnum. The distance from axial middle line to hypoglossal canal, external opening of carotid canal, and inner edge of jugular foramen was 9.78 ± 0.72, 24.50 ± 1.26, and 24.33 ± 1.68 mm, respectively. Conclusions: These data in this study are valuable for neurosurgeons in clinical practice to reduce the possibility of complications and maximize the safety of surgeries; these data also contribute to the understanding of the anatomy of craniocervical junction and its surrounding structures.